1995
DOI: 10.1002/art.1780380813
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high‐dose fish oil on rheumatoid arthritis after stopping nonsteroidal antiinflammatory drugs clinical and immune correlates

Abstract: Objective. To determine the following: 1) whether dietary supplementation with fish oil will allow the discontinuation of nonsteroidal antiinflammatory drugs (NSAIDs) in patients with rheumatoid arthritis (RA); 2) the clinical efficacy of high‐dose dietary ω3 fatty acid fish oil supplementation in RA patients; and 3) the effect of fish oil supplements on the production of multiple cytokines in this population.Methods. Sixty‐six RA patients entered a double‐blind, placebo‐controlled, prospective study of fish o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
1
5

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(120 citation statements)
references
References 28 publications
3
109
1
5
Order By: Relevance
“…2 (Espersen et al 1992) Serum IL-6 levels were unchanged in the same study (Sundrarjun et al 2004) and following 7 . 1 g EPA + DHA/d (Kremer et al 1995). In addition, no effects on serum IL-8 and IL-2 concentrations were found following fish oil supplementation in the latter study.…”
Section: Rheumatoid Arthritiscontrasting
confidence: 47%
See 1 more Smart Citation
“…2 (Espersen et al 1992) Serum IL-6 levels were unchanged in the same study (Sundrarjun et al 2004) and following 7 . 1 g EPA + DHA/d (Kremer et al 1995). In addition, no effects on serum IL-8 and IL-2 concentrations were found following fish oil supplementation in the latter study.…”
Section: Rheumatoid Arthritiscontrasting
confidence: 47%
“…9 g EPA + DHA/d in the same study. Espersen et al (1992) and Kremer et al (1995) have reported decreased serum IL-1b following 3 . 2 and 7 .…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…The fluctuations in absolute levels in all groups, including the placebo group, demonstrate the need for a proper control group in studies of this nature, and for a proper analysis that compares the effect of fish oil with that of placebo. Statistical testing of changes from baseline within the fish oil group may lead to the faulty conclusion that fish oil does decrease cytokine levels or production [3,27] In two controlled studies, no effect of dietary fish-oil on ex vivo production of IL-1b or TNF-a was found at 7 weeks and 4 months of supplementation [17,18]. Effects of n-3 fatty acids that are apparent at 6 weeks may thus 1006 W. L. BLOK et al have disappeared at 26 weeks of dietary fish oil supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation trials have been conducted for most of these diseases. Clinical trials provide good evidence of the antiinflammatory and clinical improvement effects of fish oil on rheumatoid arthritis [252][253][254] and inflammatory bowel diseases (Crohn's disease and ulcerative colitis) (ref. 255,256 ).…”
Section: Immune System Disordersmentioning
confidence: 99%